Brain and nervous system your information superhighway - Gailey, Peter; Gailey, Peter; Rogers, Carrie (New Jersey : Cambridge Educational, 2001)
This program explores the brain and nervous system, using the analogy of computers and the internet. Topics dicussesd includes electrical impulses and how nerve messages travel; parts of the brain and their function; how the brain and spinal cord are protected; the senses; and diseases, drug, and their effects on the brain and nervous system
Editor, Carrie Rogers ; executive producer, E.Ty Gardener
Keywords: Nervous System Physiology; Human physiology; Brain